Amine functionalized 3D porous organic polymer as an effective adsorbent for removing organic dyes and solvents. Issue 48 (13th June 2017) - He, Yan; Xu, Ting; Hu, Jun; Peng, Changjun; Yang, Qiang; Wang, Hualin; Liu, Honglai
Abstract : We report the application of an amine functionalized triptycene-based 3D polymer (TPP-NH2 ) as a novel adsorbent for the fast removal of organic dyes in aqueous solution and organic solvents. Abstract : Organic dyes and solvents are emerging pollutants; the development of new materials for their efficient adsorption and removal is thus of great significance. In this work, we report the application of an amine functionalized triptycene-based 3D polymer (TPP-NH2 ) as a novel adsorbent for the fast removal of organic dyes in aqueous solution and organic solvents with a view to understanding its adsorption kinetics, adsorption isotherms, desorption and adsorbent regeneration. The adsorption of organic dyes (cationic methylene blue, MEB, and anionic methyl orange, MO) on TPP-NH2 was fast, and most of the dyes were adsorbed in 60 min. The adsorption of MEB and MO follows pseudo-second-order kinetics and fits the Langmuir model, where the maximum adsorption capacity increased from 204.9 mg g −1 to 560.6 mg g −1 and 213.2 mg g −1 to 803.2 mg g −1 for MEB and MO, respectively, as the temperature increased, suggesting that the adsorption of MEB and MO on TPP-NH2 is favorable at high temperatures via an endothermic process. The pH has no obvious effect on the adsorption of MEB and MO. The used TPP-NH2 could be regenerated effectively and recycled at least five times without a significant loss of adsorption capacity. In addition, the TPP-NH2 can adsorb up to 33 times its own weight in organic solvents while wiping off the water. The high surface area, hierarchical porosity and π–π stacking interactions between the aromatic rings of MEB and MO and the aromatic rings of 3D TPP-NH2 were responsible for the efficient adsorption. Therefore, the TPP-NH2 that was synthesized using the facile strategy possesses significant potential in the treatment of wastewater.